2016
DOI: 10.1007/s10973-016-5590-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of modified keratin on the thermal properties of a cellulosic–elastomeric material

Abstract: The need for new composite materials that would exhibit good parameters such as mechanical or thermal properties, while being easily processable and able to undergo biodecomposition after its period of use, has been a great source of inspiration for modern material science. A lot of work has been done in the field of biodegradable polymeric materials throughout almost every aspects of life, from medical materials, through disposable plastic bags to materials used in agriculture. In the latter field, several sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The material should be stable for atmospheric conditions when used in crops. Similar observations have been made for cellulose-elastomeric material by Prochon and Tshela Ntumba [45]. Starch films and starchy compositions on cellulose fabrics are environmentally friendly materials, which undergo composting and biodegradation, with the potential to be used as agro-fabrics for the cultivation of crop plants.…”
Section: Discussionsupporting
confidence: 77%
“…The material should be stable for atmospheric conditions when used in crops. Similar observations have been made for cellulose-elastomeric material by Prochon and Tshela Ntumba [45]. Starch films and starchy compositions on cellulose fabrics are environmentally friendly materials, which undergo composting and biodegradation, with the potential to be used as agro-fabrics for the cultivation of crop plants.…”
Section: Discussionsupporting
confidence: 77%
“…Later on, the authors also produced a cellulosic-elastomeric material by coating cotton fibres with keratin and carboxylated styrene-butadiene latex (XSBL). They observed that the elastomeric coating increased the tensile strength and slightly increased glass transition temperature, also promoting different mechanisms of thermal decomposition, where the thermal decomposition residue was higher, in comparison to the neat cotton fabric [220].…”
Section: Butadiene Copolymer Rubbersmentioning
confidence: 99%
“…Before and after the aging procedure, the tensile strength (TS) and the elongation at break (EB) were examined. The aging factor (A f ) was determined from the following relationship [42]:…”
Section: Methodsmentioning
confidence: 99%